Photocatalytic oxidation of laundry industry wastewater using TiO2 as catalyst and UV1 light (2005)
The treated effluents are wastewater supplied by a laundry industry, using photocatalysis technology with artificial sources of radiation (UV lamps), TiO2 as a catalyst and a composite parabolic trough cylinder (CPC). Industrial wastewater was used with the aim of starting an investigation with real liquid effluents and not with synthetic mixtures prepared in the laboratory, what is sought with this project is to take a first step towards the use of these new technologies on an industrial scale . The experimental results were statistically processed by response surface model, taking the catalyst concentration, pH and recirculation time, as the parameters that affect the final concentration of COD (Chemical Oxygen Demand), the response variable chosen. A maximum degradation without H2O2 of 26.49% and with the addition of H2O2 of 41.8% was achieved.